Exploring the power flow solution space boundary. - Hiskens, I.A (IEEE Transactions on power systems)
A knowledge of the structure of the boundary of solutions of the power flow problem is important when analyzing the robustness of operating points. This paper proposes a predictor-corrector technique to assist in exploring that structure. Points on the solution boundary satisfy the power flow equations together with an equation which forces the power flow Jacobian to be singular. Curves of such points result from freeing two parameters of the system. The proposed technique follows those curves. A simple example is used to illustrate the complex nature of the power flow solution space